Fazekas Mihály: csillagászat és kortan - Zsoldos, Endre (Studia Litteraria, 2020)
It is less known that the poet Mihály Fazekas was interested in astronomy and even published a calendar of his own. The Debreczeni Magyar Kalendariom (“Hungarian Calendar of Debrecen”) was a successful venture, surviving its founder by decades. Instead of the usual prognostications one finds in such calendars, Fazekas published popular astronomical articles of varying length. In these he described the properties of the members of the Solar System, gave their distance from the Earth, their periods, sizes etc. His point of view was definitely modern. Despite some errors originating probably from oversimplification, the calendar provided his readers with current information on the planets. His unpublished manuscripts confirm that he was well versed in mathematical calculations.